Genome-wide association study of renal cell carcinoma identifies two susceptibility loci on 2p21 and 11q13.3. - Purdue, M; Johansson, M; Zelenika, D; Toro, JR; Scelo, G; Moore, L; Prokhortchouk, E; Wu, X; Kiemeney, L; Gaborieau, V; Jacobs, K; Chow, W; et al. (2011)
We conducted a two-stage genome-wide association study of renal cell carcinoma (RCC) in 3,772 affected individuals (cases) and 8,505 controls of European background from 11 studies and followed up 6 SNPs in 3 replication studies of 2,198 cases and 4,918 controls. Two loci on the regions of 2p21 and 11q13.3 were associated with RCC susceptibility below genome-wide significance. Two correlated variants (r² = 0.99 in controls), rs11894252 (P = 1.8 × 10⁻⁸) and rs7579899 (P = 2.3 × 10⁻⁹), map to EPAS1 on 2p21, which encodes hypoxia-inducible-factor-2 alpha, a transcription factor previously implicated in RCC. The second locus, rs7105934, at 11q13.3, contains no characterized genes (P = 7.8 × 10⁻¹⁴). In addition, we observed a promising association on 12q24.31 for rs4765623, which maps to SCARB1, the scavenger receptor class B, member 1 gene (P = 2.6 × 10⁻⁸). Our study reports previously unidentified genomic regions associated with RCC risk that may lead to new etiological insights.